Identifikasi Diskalkulia Pada Siswa Sekolah Dasar Dalam Materi Penjumlahan Dan Pengurangan - Khoiri, A. Wasil; Lutfiyah, Lutfiyah; Sulisawati, Dwi Noviani (Universitas Islam Jember, 2025)
Learning difficulties are commonly found in students from the lowest level of education to higher education. In elementary school children, there are many learning difficulties, the causes of which are different for each individual. Dyscalculia is one of the learning problems in Mathematics. The purpose of this study is to determine dyscalculia in elementary school students in addition and subtraction material. This type of research is descriptive qualitative. The subject of this research is first grade students of Keronegoro 01 Elementary School in the 2024/2025 school year as many as 2 students. The results of the research identify elementary school students obtained from observation, test, and interview data. The dyscalculia that occurs in A1 is pre-cognostic dyscalculia, intermediate dyscalculia, graphic dyscalculia, lexical dyscalculia, and qualitative dyscalculia. While the dyscalculia experienced by A2 is indiagnostic dyscalculia. Keywords: dyscalculia, addition and subtraction